Essays on ceremonial - Atchley, E. G. Cuthbert F.; Legg, J. Wickham; Dearmer, Percy; Bishop, Edmund (Library of liturgiology & ecclesiology for English readers, 1904)
English ceremonial / by E.G. Cuthbert F. Atchley -- On some ancient liturgical customs now falling into disuse / by J. Wickham Legg -- On English liturgical colours / by E.G. Cuthbert F. Atchley -- Church vestments / by Percy Dearmer -- The altar and its furniture / by Percy Dearmer -- Some remarks on the Edwardian prayer-book / by E.G. Cuthbert F. Atchley -- The genius of the Roman rite / by Edmund Bishop.